The Cat–Owner Relationship: Validation of the Italian C/DORS for Cat Owners and Correlation with the LAPS - Carmen Borrelli; Giacomo Riggio; Tiffani Josey Howell; Patrizia Piotti; Silvana Diverio; Mariangela Albertini; Paolo Mongillo; Lieta Marinelli; Paolo Baragli; Francesco Paolo Di Iacovo; Angelo Gazzano; Federica Pirrone; et al. (Animals, 2022)
Globally, most people now own a pet. Scales have been developed to understand the impact of pet ownership on people’s lives and to measure specific aspects of the owner–pet relationship. The Cat-/Dog-Owner Relationship Scale (C/DORS) is a tool developed to investigate this relationship in both dog and cat owners. The aim of the study was to refine and validate the C/DORS for cat owners in Italian. Exploratory Factor Analysis and Confirmatory Factor Analysis (CFA) were used to determine the most appropriate factor model. Construct validity was confirmed by correlating the C/DORS subscales with the Lexington Attachment to Pets (LAPS) subscales. Results confirmed the original structure of the English version (i.e., three factors: Pet Owner Interaction = POI, Perceived Emotional Closeness = PEC, Perceived Costs = PC) and CFA confirmed the structure of LAPS and C/DORS scales. Cronbach’s alpha demonstrated the Italian version of the two scales to have good internal reliability for all domains. Owners of cats living exclusively indoors reported higher scores on POI and PEC compared to indoor/outdoor cats. Owning both cats and dogs was correlated with lower scores on POI, and fewer perceived costs (i.e., PC) of cat ownership. Finally, behaviour problems, not being neutered, and lack of previous experience with cat ownership were associated with lower scores on PC.